Finding cost-effective nutrient solutions and evaluating environmental conditions for biogasifying bituminous coal to methane ex situ. (1st March 2016) - Zhang, Ji; Park, Stephen Y.; Liang, Yanna; Harpalani, Satya
Highlights: Composition of the nutrient solution is critical for microbial communities gasifying coal to methane. Different environmental parameters need to be evaluated regarding their effects on methane production. A methane yield of 828.9 ft 3 /ton was observed in 30 days from bituminous coal. Abstract: Biostimulation through providing nutrients to microorganisms has been proven to be highly effective in enhancing methane yield from bituminous coals in the Illinois basin. In light of the extremely cheap natural gas price at present, it is critically important to decrease the cost of nutrient solutions used to stimulate microbial gasification of coal and improve the cost-effectiveness of the biostimulation approach. To lower cost of a nutrient solution reported in previous studies, the three most expensive components, yeast extract, peptone and mercaptoethanesulfonic acid (Coenzyme M, CoM) were evaluated. Regarding the first two, decreasing their concentrations resulted in decreased methane production. In terms of CoM, its concentration could be reduced to at least half without affecting methane yield negatively. Complete elimination of CoM led to a methane yield of 85% of those with the presence of this compound in the original medium. Two complex media, trypticase soy broth (TSB) and corn steep liquor (CSL) were intended to replace yeast extract and peptone. TSB had increasingly positive effect with increasing its concentration while CSL had opposite trend. TSB at 100% (v/v) was then investigated under different cultivation conditions. Among the four parameters tested, TSB concentration and agitation were found to exert positive effect while coal loading and temperature had negative impact on methane production. The highest methane yield of 828.9 ft 3 /ton in 30 days was obtained under temperature of 28 °C with a coal loading of 200 g/L and agitation at 100 rpm. This yield is four-time higher than those observed with the original medium. These results clearly demonstrated that biostimulation is a viable method for enhancing methane production from coal and the ingredients of nutrient solutions need to be evaluated in detail in order to make biostimulation cost-effectively at commercial scales.